Challenges and Initiatives on Single-Use Plastics in Universities - Khlaraize Seblos; Dennivel Tabañag; Charles Sangcap; C. N. Ocampo; F.D. Tapdasan; Jennifer Paño (Journal of Social Science, 2023)
Single- Use Plastic manufacturing and use have risen steadily since its invention, spurred by the rising urbanization of the world. Ever since its introduction, and driven by rapid urbanization, there has been an increase of plastic production and consumption. The government, organizations, and other institutions should perform various investigations to explore the many limits, in any aspects, in order to address plastic waste and its underlying problems. It involves implementing many strategies and efforts throughout the entire community, including in institutions. A meta-synthesis of the challenges and initiatives faced by schools with relation to single-use plastics is essential to providing a complete awareness of the existing situation and development of sustainable practices in educational institutions. After extensive investigation of the synthesized articles the challenges were categorized into seven themes: manpower, equipment/facility and space, administrative support, financial, lack of information dissemination, attitude/behavior, and curriculum integration. Meanwhile, the initiatives were classified into six themes: environmental goals, rewards and motivation, disciplinary measures, knowledge and awareness, educational approach, and the equipment and facilities. This meta-synthesis concluded that the various difficulties faced by universities in managing single-use plastic hinder the implementation of those solutions as well as the various initiatives employed by universities to promote the spread of environmentally conscious and responsible people. School administration and teachers collaborate in integrating the reduction of plastic waste to the teaching instruction. In addition, incentives and disciplinary actions are among the finest ways to instill routines, practices, and habits in the reduction and generation of plastic trash. To lay a solid basis for environmental education and awareness, policies that set expectations for behavior and offer direction to faculty, staff, and students are established.